2007
DOI: 10.1007/s10995-007-0287-z
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum Depression: Racial Differences and Ethnic Disparities in a Tri-racial and Bi-ethnic Population

Abstract: Statistically, postpartum depression can be ranked from high to low as Native Americans, Whites, African Americans and Hispanics (Hispanics have remarkably lower depression rates). This information is critically important to clinicians, researchers, agency administrators and social workers who work with these populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 15 publications
1
27
1
Order By: Relevance
“…Confidence intervals of the rates of major and minor depression by group were estimated (Table 2), followed by statistical tests to first determine the differences among these rates and then explore the differences in variations of full scores and differences in mean full scores www.intechopen.com between groups. Risk assessment was performed with factor analysis and correlation methods (Wei et al, 2008 The major factors (and their components -original 35 factors in the PDSS holding loadings larger than 0.70; factor loadings less than 0.40 dropped; standard regression coefficients used) were identified according to the order of significance where italic (component) factors had average ratings of "agree" or "strongly agree" from the 90 likely major depressive participants. The Henry Kaiser's eigenvalue-based rule (Rule of Thumb) was used: The total number of factors is chosen as the number of eigenvalues of the correlation matrix that are larger than one (Morrison, 1990).…”
Section: Data Analysis Methods and Software Toolsmentioning
confidence: 99%
See 4 more Smart Citations
“…Confidence intervals of the rates of major and minor depression by group were estimated (Table 2), followed by statistical tests to first determine the differences among these rates and then explore the differences in variations of full scores and differences in mean full scores www.intechopen.com between groups. Risk assessment was performed with factor analysis and correlation methods (Wei et al, 2008 The major factors (and their components -original 35 factors in the PDSS holding loadings larger than 0.70; factor loadings less than 0.40 dropped; standard regression coefficients used) were identified according to the order of significance where italic (component) factors had average ratings of "agree" or "strongly agree" from the 90 likely major depressive participants. The Henry Kaiser's eigenvalue-based rule (Rule of Thumb) was used: The total number of factors is chosen as the number of eigenvalues of the correlation matrix that are larger than one (Morrison, 1990).…”
Section: Data Analysis Methods and Software Toolsmentioning
confidence: 99%
“…Major dissimilarities existed between the Hispanic group and the non-Hispanic group (Wei et al, 2008). The prevalence of depression at six weeks postpartum in a rural triracial population using the Beck and Gable PDSS found that Native American women had the highest rate of major depression (18.7%) and average rates of minor depression (10.5%).…”
Section: Racial Differences and Ethnic Disparities (586 Women)mentioning
confidence: 98%
See 3 more Smart Citations